HYDROLOGICAL STUDIES IN THE INSHORE WATERS OF MANGALORE DURING 1964-1973 - Radhakrishnan, N S (Indian Journal of Fisheries, 2011)
Observations on the hydrological conditions over a decade of the inshore waters of Mangalore are presented and discussed, with an emphasis on the effects of the southwest monsoon in modifying the hydrographic characteristics. The annual variation of temperature was bimodal with peaks occurring prior to the two monsoon periods, and the minimum occurring during the monsoons. The salinity and pH indicated a sharp fall during the southwest monsoon period, and the phosphate and silicate contents exhibited a remarkable increase during the same period. The dissolved oxygen contents also showed a decline during the southwest monsoon period.